4P Marketing Strategy In Creative Economy In Kandri Village - Nina Mistriani; Trenggono Trenggono; Haniek Listyorini; Ibtihal Zulfa Septi Ronaa Bintang Setyoning Nugrohoputri; Danang Aji Muhamad dewa; Lilis Suciati; Iklima Raissa Adristi Prasista; Taufik Mahzan (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Creative economy products have the ability to market and strengthen quality and competitive products. Marketing of MSME products of chips and cassava centers in Semarang City is a leading center in tourist villages. Local community products that are worth selling. The purpose of this research is to produce a creative economic development model through product marketing that collaborates with various aspects. This type of research uses qualitative research methods with case study research design. Data collection techniques using observation, interview and documentation techniques. The results of the 4P marketing strategy research were successfully applied effectively in marketing in the tourism business as an educational tour and community economic improvement.